EpApp: Development and evaluation of a smartphone/tablet app for adolescents with epilepsy. (April 2018) - Le Marne, Fleur A.; Butler, Sharlene; Beavis, Erin; Gill, Deepak; Bye, Ann M.E.
Highlights: This study evaluated a smartphone application for adolescents with epilepsy. The app significantly improved epilepsy knowledge and medication management. The app was well received in terms of design, content, usability and functionality. Education messages can be revisited at user's discretion to aid learning. App portability allows 24 h access to medication reminders and medical profile. Abstract: The study aimed to comprehensively evaluate a mobile application (EpApp), designed with stakeholder input, to educate and facilitate management of adolescents with epilepsy. A prospective cohort of adolescents with epilepsy (13–19 years) and their parent/carer participated between June 2015 and December 2016. Primary outcome measure was knowledge acquisition. Secondary outcomes were psychosocial variables (attitude towards illness and seizure self-efficacy) and clinical parameters (medication adherence, seizure burden). Functionality, design, content and app utility were appraised via survey and open-ended questions. 51 adolescents completed baseline surveys (mean age 14.49 years), 36 follow-up surveys. Both self and general epilepsy knowledge increased following intervention (p ≤ 0.005). Significantly fewer medication reminders were required during intervention (M = 2.93, p = .002) and follow-up (M = 3.54, p = .030) compared to baseline (M = 6.64). Measures of app design, content, functionality and utility were very favourable. There was no significant improvement in seizure burden, or psychosocial parameters. Educational page-visits reflected interests and concerns. This study demonstrates that EpApp increases knowledge and is engaging. The app is available free, internationally via Android/Apple platforms.